Examining Gender Inequality in Ugandan Newsrooms: A Case of Power Fm - Racheal Atuhaire (Uganda Christian University, 2024)
Gender inequality is a prevalent issue in Ugandan newsrooms, with men being dominant, women less represented and at a high chance of facing harassments in the work environment. This research focuses on gender dynamics in Uganda’s newsrooms with special attention to Power FM. From feminist theory perspective, this topic investigates the issue of women representation in leadership positions, gender bias in news content as well as experiences that female journalists undergo. The outcomes indicate a wide gap between men and women journalists perpetuating stereotypes about gender and limiting opportunities for females. The study therefore calls for policies and practices that are sensitive to gender dimensions so as to redress systemic gender inequality within Uganda’s media industry. It contributes to the ongoing dialogue on media and gender by emphasizing how inclusive newsrooms promote diversity of views while ensuring equal representation. The suggestions given by this study might benefit individuals working towards achieving fairer media systems both inside Uganda and at international levels like researchers, practitioners and policy makers. Particularly, some strategies would be suggested based on findings from this research for consideration. I.e. increasing women’s representation in leadership positions, addressing gender bias in news coverage, and creating a more supportive work environment for female workers. This study has reviewed gender inequalities that exist within Ugandan newsrooms using a specific case of Power FM. Using representation, opportunity, and treatment of women working at the place as measures, the research found vast differences that exist in this company owing to a lack of diversity and perpetuation of stereotypes and biases based on gender. The data are showing underrepresentation in leadership positions, discrimination on gender grounds, stereotypical reporting of women.